GAMBARAN STATUS GIZI REMAJA SISWA DI KABUPATEN SEMARANG - Yuliaji Siswanto; Ita Puji Lestari (Pro Health Jurnal Ilmiah Kesehatan, 2021)
The nutritional status of adolescents in Central Java is still not balanced because there are still adolescents who require low nutritional status and obesity and even achieve nutrition due to excessive nutritional status. This study discusses the nutritional status of adolescent high school students in Semarang Regency. This study aims to determine the nutritional status of adolescent high school students in Semarang Regency. The research design used is descriptive, using a cross sectional approach. The sample in this study were 138 students using cluster random sampling techniques. Grouping nutritional status data using BMI/U and z-score categories, processing this data using univariate tests. The results showed that most high school students had normal nutritional status, that is 104 students (75.36%), 28 students fat (20.29%), and 6 students obesity (4.35%). The problem of excess nutrition mostly occurs in adolescent girls, namely the obesity nutritional status of 5 students (6.3%) and 17 students fat (21.5%). From the results of this study it can be concluded that the nutritional problems that occur are obesity and obesity which still have a fairly high percentage of adolescent girls.